Evolution of Sleep Apnea and Arousals in Patients with Ischemic Stroke: A Longitudinal Follow-Up Study - PR Srijithesh; Sivasubramanian Mythirayee; Doniparthi Venkata Seshagiri; Nitish L Kamble; Sanjib Sinha; Ravi Yadav (Annals of Indian Academy of Neurology)
Background and Objectives: Sleep-disordered breathing (SDB) is characterized by pauses or shallow breathing during sleep. It is linked to poorer outcomes and increased stroke recurrence in stroke patients. We aimed to evaluate the proportion, severity, type, and evolution of SDB and arousals in ischemic stroke patients. Methods: Ischemic stroke patients were recruited to evaluate SDB. Patients underwent overnight polysomnography (PSG) twice – within 1 month of stroke onset and again after 3 months. Clinical outcomes were evaluated at 6, 18, and 24 months. Results: Of 141 acute ischemic stroke patients screened, 111 patients recruited in the study and 105 patients had technically adequate polysomnography. The mean age of patients was 50.5 years (standard deviation [SD]: 12.30), 78.4% of the patients were males, and the mean body mass index was 26 (SD: 5.4). Results showed that 81.9% had an apnea–hypopnea index (AHI) ≥5, with 12.5% having an AHI >30. The median arousal index (ArI) was 15.4 (interquartile range [IQR]: 0.5–50.5), which increased as the apnea increased. During follow-up, 56.8% patients had an AHI ≥5, with 12.5% having severe apnea. The median ArI decreased from 15.4 (IQR: 0.5–50.5) initially to 11.54 (IQR: 0.5-21.1) at follow-up. Numerical change in AHI severity categories were noted during the follow-up (mild: 8 vs 15; moderate: 17 vs 11; severe 19vs 7). For AHI >30, ArI decreased from 24.63 (IQR: 0.7-50.05) to 10.54 (IQR: 7.1-15.07) at follow-up. Sleep efficiency and rapid eye movement (REM) sleep duration increased on follow-up. Conclusions: The study showed a high proportion of SDB in acute ischemic stroke patients. In the follow-up, SDB improved, as reflected in AHI and ArI changes.